LAXATIVE ACTIVITY OF RAPHANUS SATIVUS L. LEAF - Dande, Payal; Vaidya, Abhishek; Arora, Pratiksha (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The aim of the study was to evaluate the laxative activity of Raphanus sativus L. leaf. Methods: Aqueous extract (AqRS) and fresh juice (FreRS) of Raphanus sativus L. were prepared and evaluated by preliminary phytochemical test. Laxative action of the extract at a dose of 250, 500 and 750 mg/kg (p.o) was evaluated using wistar albino rats, weighing 200-300 g, in different experimental model such as loperamide induced constipation, laxative activity test, gastrointestinal motility test, water and electrolyte secretion test. Results: Preliminary phytochemical studies carried for AqRS extract and FreRS juice of R.sativus leaves revealed the presence of carbohydrates, tannins, phytosterols, flavonoids and saponins. The FreRS juice & AqRS extract at 750mg/kg showed significant increased in fecal output in loperamide induced constipation (p<0.05) and laxative activity test (p<0.01). Both extract and the juice increased the distance covered in charcoal meal test (p<0.001) and increased the water-ion secretion in electrolyte secretion test (p<0.001) indicating laxative activity of Raphanus sativus leaf. Conclusion: The present study revealed that the aqueous extract (AqRS) and fresh juice (FreRS) of Raphanus sativus L. at a higher dose of 750 mg/kg exhibit significant laxative activity. Â KEY WORDS: Laxative, Raphanus sativus, Loperamide, Constipation